Methods for Increasing the Vocabulary of Primary School Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
The development of students’ speech is primarily connected with enriching their vocabulary. Working on vocabulary plays a significant practical role in increasing word stock. In the process of conducting vocabulary work based on the studied text, students become practically familiar with archaic words, newly coined words, profession-related vocabulary, dialectal words, and words characteristic of the literary style. This article presents information on methods for increasing the vocabulary of primary school students.